The Effect of Training Methods and Eye-foot Coordination on the Dribbling Skills of Diklat Bintang Pelajar Players (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The development of modern football, technical level, physical condition and tactical development are studied in depth and scientifically carefully. Technical factors are the most vital in football, including the technique of dribbling. The dribbling training method used needs to be studied to determine whether or not it affects the athlete's dribbling ability. The purpose of this study was to analyze the effect of training methods and eye-foot coordination on the dribbling skills of student star training players. The method used is an experimental method with a factorial design in the form of a pretest posttest group with a sample of 40 football athletes. The analysis technique used is normality test, homogeneity test, and hypothesis testing. The results of this study are that there is an influence between the Massed Practice training method with an average value of 43.75 and the Distributed Practice training method obtained an average value of 42.00 on dribbling skills. There is an effect of eye-foot coordination on dribbling skills. Athletes who have high eye-foot coordination with an average score of 14,5500 and athletes who have low eye-foot coordination with an average score of 10,700. There is an interaction between the Massed practice and Distributed Practice training methods on the dribbling skills of the Bintang Pelajar Training players in Semarang Regency. The conclusion of this study is that there is an influence and interaction between the training methods and eye-foot coordination on the dribbling skills of the Bintang Pelajar training players, Semarang Regency.